Indywidualizacja a system w postępowaniu penitencjarnym w świetle kodeksu karnego wykonawczego - Rondalska, Dorota (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is devoted to the principle of penitentiary proceedings for individuals during the implementation of imprisonment and its coherence with executive systems. The author analyzes both the concept and the content of this principle. She also discusses how it is articulated in the Executive Penal Code. As a result, the article states that this is institutional individualization. In this context, it considers how individualization is consistent with standardized systems of implementation for punishment. It draws atten-tion to various system definitions in Polish penitentiary literature. It estimates that only the system of “programmed impact” creates full conditions for combining (in practice) the level of the system with the level of the individual, i.e. a particular convict. Finally, it states that the title of Section 3 of the Criminal Code is formulated incorrectly, because it can be read that it is about the individualization of punishment, and not about dealing with the convict. This makes it quite difficult to unequivocally assess the way in which solutions aimed at implementing the principle of individualization of imprisonment in prisons are implemented.
Keywords: indywidualizacja; kara; wykonanie kary; zakład karny; wykonawczy kodeks karny